Chemical-Affinity Disparity and Exclusivity Drive Atomic Segregation, Short-Range Ordering, and Cluster Formation in High-Entropy Alloys. (March 2021) - Chen, Shuai; Aitken, Zachary H.; Pattamatta, Subrahmanyam; Wu, Zhaoxuan; Yu, Zhi Gen; Banerjee, Rajarshi; Srolovitz, David J.; Liaw, Peter K.; Zhang, Yong-Wei
ABSTRACT: Recently, atomic segregation, short-range ordering, and cluster formation have been observed experimentally in high-entropy alloys (HEAs). Differences in the atomic size and electronegativity of constituent elements were proposed to be the underlying cause of such ordering. Here, we investigated two HEAs, CoCuFeNiPd and CoCuFeNiTi, using a combination of Monte Carlo and molecular dynamic simulations. Our results show that the CoCuFeNiPd HEA exhibits much stronger atomic segregation and short-range ordering than the CoCuFeNiTi HEA, despite the larger differences in the relative atomic size and electronegativity of Ti with other constituent elements, as compared to those of Pd, suggesting that the differences in the atomic size and electronegativity alone are insufficient to explain the simulation results. We find that it is the chemical-affinity disparity and exclusivity between Ti (Pd) with the remaining species that lead to the different clustering behavior in these two HEAs. Specifically, three conditions for strong atomic segregation and short-range ordering are identified: 1. a large chemical-affinity disparity amongst the chemical elements; 2. a high chemical-element exclusivity in low-, medium-, and high-energy clusters; and 3. a net energy reduction associated with low- and medium-energy-cluster formation that compensates for the energy increase associated with high-energy-cluster formation. Our findings are in agreement with experimental results reported in literature, and highlight the importance of chemical-affinity disparity and exclusivity in influencing the microstructure of HEAs, explain the origin of high-energy-cluster formation in HEAs, and provide guidelines for designing HEAs with excellent properties. Graphical abstract: Image, graphical abstract